2014
DOI: 10.1056/nejmoa1408214
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control and Excess Mortality in Type 1 Diabetes

Abstract: In our registry-based observational study, patients with type 1 diabetes and a glycated hemoglobin level of 6.9% or lower had a risk of death from any cause or from cardiovascular causes that was twice as high as the risk for matched controls. (Funded by the Swedish Society of Medicine and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
622
5
28

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 784 publications
(681 citation statements)
references
References 28 publications
26
622
5
28
Order By: Relevance
“…Interestingly, all‐cause mortality, and the combined outcome (stroke and death), were only slightly increased in type 2 diabetes patients compared to patients without diabetes. Others have demonstrated an increased risk of death in type 1 diabetes patients 27, 28. In a nationwide study, based on data from the Swedish National Diabetes Register, it was found that type 1 diabetes individuals, even at optimal glycemic control, had twice as high a risk of death, predominantly from CVD, compared to matched controls from the general population 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, all‐cause mortality, and the combined outcome (stroke and death), were only slightly increased in type 2 diabetes patients compared to patients without diabetes. Others have demonstrated an increased risk of death in type 1 diabetes patients 27, 28. In a nationwide study, based on data from the Swedish National Diabetes Register, it was found that type 1 diabetes individuals, even at optimal glycemic control, had twice as high a risk of death, predominantly from CVD, compared to matched controls from the general population 27.…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated an increased risk of death in type 1 diabetes patients 27, 28. In a nationwide study, based on data from the Swedish National Diabetes Register, it was found that type 1 diabetes individuals, even at optimal glycemic control, had twice as high a risk of death, predominantly from CVD, compared to matched controls from the general population 27. When myocardial infarction, stroke, and heart failure are reported as separate outcomes in individuals with diabetes, usually coronary heart disease is predominant 29.…”
Section: Discussionmentioning
confidence: 99%
“…2 More recently, data from the Swedish National Diabetes Registry found that patients with type 1 diabetes and glycated hemoglobin (A1c) levels of 6.9% (below current ADA Clinical Practice Recommendations) had twice the mortality as age-matched cohorts without diabetes. 3 In patients in the Swedish National Registry, 14.5% of all mortality was attributed to diabetic ketoacidosis or severe hypoglycemia. Among patients younger than 30 years, 31.4% of all premature mortality was attributed to diabetic ketoacidosis or severe hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to well-described chronic complications, higher HbA1c is associated with increased mortality in both the DCCT-EDIC study group and in a Swedish population-based study of persons with type 1 diabetes compared with controls. 17,18 In the DCCT-EDIC mortality study, intensive insulin therapy nearly obliterated the difference in cardiovascular outcomes at 30 years of follow-up, but in the full cohort, a 10% higher HbA1c was associated with a 56% increase in the risk of mortality. 17,19,20 Reports from Scotland, Australia, and Norway show that both acute and chronic complications of diabetes contribute to the excess mortality in persons with type 1 diabetes.…”
Section: Cgm In Type 1 Diabetes Treated With MDImentioning
confidence: 99%